Avaliação da fertilidade e de possíveis defeitos estruturais externos sobre a prole de ratos machos expostos cronicamente ao arsênio - Oliveira, Rodrigo Juliano [UNESP]; Oliva, Samara U.; Daroz, Gisela A. [UNESP]; Rúbio, Eliana M. [UNESP] (My University, 2005)
Arsenic is an environmental pollutant that influences the male reproductive function, affecting the spermatogenesis process in the testis and causing alterations in the sperm. The objective of this work was evaluate the reproductive efficiency in adult male rats exposed to arsenic and the possible male-mediated structural malformations. The animal were treated with sodium arsenato (3,6 mg/Kg, i.p.), twice a weak, for 15, 30, 45, 60 or 75 days whereas control received only distilled water. Results have showed a reduced pregnancy rate associated to a decrease in the fertility potencial and to a increase in the preimplantation loss. There was a decrease in the fetal weights, as showed by its average. Malformations rate, postimplantation loss and resorptions were unaffect by treatment. These results suggest that chronic exposure to arsenic provokes reduction on fertility of male rats. Further studies are required to clarify the arsenic effects on male reproductive system and male-mediated effects on progeny.
Fertility assessment and possible external structural defects on progeny from male rats chronically exposed to arsenic
Keywords: Arsenic; Fertility; Malformation; Progeny; Rats; Reproductive effects; arsenate sodium; arsenic; water; conference paper; congenital malformation; controlled study; embryo resorption; fetus weight; long term exposure; male; male fertility; nidation; nonhuman; pollution; pregnancy rate; preimplantation embryo; progeny; rat; reproductive effort; subfertility; Animalia